Dynamical reliability analysis and remaining useful life prediction for an on-orbit satellite camera. (August 2022) - Xie, Jingyan; Li, Yun-Ze; Yang, Lizhu; Sun, Yuehang; Yuan, Man; Ye, Binpeng
Launch missions of small satellites have been increasing in recent years. As the main payload, the camera plays a pivotal role in remote sensing detection. Therefore, on-orbit health estimation is a continuous concern for satellite design. This study aims to develop a dynamic intelligent health estimation algorithm for the on-orbit satellite camera. Based on fuzzy theory in the intelligent health estimation algorithm, the reliability and the remaining useful life are transformed into a newly defined health estimation index, namely "health vector, " which reflects camera health from the aspects of the electrical and mechanical parts. Compared with traditional methods, the new intelligent health estimation algorithm can not only judge the development direction of satellite camera's health status, but also predict the degree of change. In addition, the proposed "health vector" is concise for engineers to monitor the health status of satellites in real time from the ground in multiple dimensions. In summary, this study provides a new method for on-orbit health management of satellite cameras.